Pelatihan komunikasi efektif kepada petugas dapat menurunkan keluhan tambahan biaya naik kelas rawat inap pada pasien BPJS/JKN (Studi kasus di RS.X Malang) - Erwanto, Erwanto; Koeswo, Mulyatim (Journal Nursing Care and Biomolecular, 2018)
RS. X (Islamic Hospital) Malang has been cooperating with BPJS Kesehatan (National Health Care Security) Â since 2014. During the period of January to September 2017 there are 100-110 complaints from patients regarding the additional cost of BPJS who are upgrading classes. One of the reason is the lack of understanding of patients toward information provided by officers of IDP inpatient room. The objective of this study was to determine the difference before and after the training of effective communication of patientsâ complaints. Research with fake experimental methods by comparing before and after training of IDP inpatient room officers. The number of respondents was total number of BPJS inpatients who were upgrading class in a month, in September as many as 24 respondents and in October was 61 respondents. Samples were taken purposively, and data were collected through questionnaires administered to patients underwent hospitalization during the periods of September and October 2017, as well as communication observations toward officers. Data analysis was descriptive of the difference of officersâ effective communication indicator and patient complaint between before and after training. The results of the research showed that there were differences in patient complaints regarding the additional cost of upgrading, from 46% before training to 5% after the training. The conclusion of the research was the effective communication of the officer might decreased BPJS Kesehatan patientsâ complaints regarding the additional cost of upgrading the treatment class.